How feminist legal theory can help to safeguard the rights and interests of disadvantaged women and girls during crises: lessons from the COVID-19 pandemic and South Africa - Pitt, Jordan Chloe (Department of Public Law, 2025)
Periods of global and national crisis have a tendency to upend progress made with respect to women's and girls' equality. Laws and policies created during these periods, seemingly neutral on their face, are often hastily constructed in a bid to ensure swift crisis management and an amelioration of immediate harm. These policies, however, fail to take into account the unique lived realities of women and girls, in general, and disadvantaged women and girls, in particular. Such oversight results in the unfavourable inevitability that they will be prevented from enjoying rights and freedoms on an equal basis with men. The COVID-19 pandemic represents a manifestation of such a crisis scenario as the measures employed by governments to deal with the virus have resulted in the exacerbation of already-existing gender inequalities, risks and vulnerabilities. This dissertation seeks to investigate South Africa's response to the COVID-19 pandemic as a case study of a crisis and the adverse impact of this response on the rights and interests of disadvantaged women and girls in the country. A feminist lens, in the form of Feminist Legal Theory, is used to elucidate this disproportionate impact. In order to assess and evaluate South Africa's response, this dissertation analyses the obligations that are placed on State parties to ensure the protection of women's equality during crises as they are contained in regional and international human rights instruments. With a particular focus on the Convention on the Elimination of Discrimination Against Women, the Maputo Protocol and the recommendations of their respective institutional bodies, this dissertation finds that there is a clear duty on State parties to take positive steps to implement and create gender-responsive mitigation measures to ensure that virus-containment strategies do not result in discrimination along gendered and socioeconomic lines, albeit indirectly. Having regard to these obligations, this dissertation finds that South Africa has failed to adequately safeguard the rights of its women and girls during this crisis. The government's mitigation policies in various sectors were either absent, gender-blind, or not sufficiently responsive so as to ensure adequate protection of the rights of women and girls as a heterogenous group. Lessons gleaned from South Africa reveal a pressing need for the inclusion and amplification of the voices of the most vulnerable in future crisis decision-making.